Phase formation in surface layers of GaTe and InTe single crystals during thermal oxidation in air - Balitskii, O.A.; Savchyn, V.P.; Savchyn, P.V.; Fiyala, Ya.M. (Functional Materials, 2004)
The oxidation processes of indium and gallium monotellurides have been discussed. The oxidation has been established to result in formation of additional phases with higher tellurium content, namely, gallium and indium sesquitellurides, respectively.